(untitled) (Our Nature, 2013)
The White-eared Bulbul Pycnonotus leucotis is found mostly in the desert-dry lowlands from Afghanistan, Pakistan, Iraq, Iran, Bahrain, and in the northern parts of India. This bulbul has a medium gray body, jet black head; subtle rounded black crest and a distinct white patch over the ear coverts, hence the name. Feet and legs are mottled dark gray/brown. DOI: http://dx.doi.org/10.3126/on.v10i1.7798